EXPRESSION OF MODIFIED RECOMBINANT HUMAN ERYTHROPOIETIN IN CHO-K1 CELLS AND ITS IN VITRO PROLIFERATION ASSAY IN TF-1 CELLS - Adi Santoso; Endah Puji Septisetyani; Edy Meiyanto; Dyaningtyas D.P. Putri; Ratih Asma Ningrum (Universitas Gadjah Mada, 2014)
Erythropoietin (EPO) is a 30 kDa glycoprotein hormone which is important for red blood cells maturation. EPO consists of 165 amino acids and possesses 3N-linked carbohydrate chains. Recombinant human erythropoietin (rHuEPO), such as epoetin-α and epoetin-β, have been used for many years to treat anemia in patients with chronic renal failure, systolic heart failure, HIVAIDS, or cancer. In vivo stability of rHuEPOs were low due to rapid metabolisms by galactosyl receptor of the hepatocytes. Previously, a novel erythropoiesis stimulating protein (NESP) called darbapoetin-α (DARB) which possesses two additional Nlinked glycosylation had been studied. It was observed that NESP showed better in vivo stability and biological activity compared to the unmodified form (containing only 3N-linked carbohydrate chains). Based on the above study, we attempted to synthesize recombinant human EPO (rHuEPO) by generating CHO-K1 cell lines expressing codon-optimized human epo open reading frame (ORF) in CHO-K1 cells. The ORF was modified to contain 5 Nlinked carbohydrate chains. The media obtained from CHO-K1 cell culture was collected and diafiltrated with the use of tangential flow filtration. The rHuEPO protein containing polyhistidine tag was purified using affinity chromatography. An SDS/PAGE and Western blotting analyses confirmed that the purified protein was the modified rHuEPO. MTT based proliferation assay was conducted in TF-1 bone marrow cell line as a model. The result showed that the modified rHuEPO was able to enhance TF-1 cells proliferation.